SURAU DAN MODERNISASI PENDIDIKAN DI MASA HINDIA BELANDA - MEIMUNAH S MOENADA (Sosial Budaya, 2011)
Mosque is one little building that in origin is built for forbear repression. With its Islamic coming, mosque experiences to process Islamisasi. Mosque terminology then pointing to at one particular” little mosque ”, one that usually doesn't be utilized for sholat Jum at. And succeeding mosque at West Sumatra, have two functions, first as logistic as custom, and both of religion function, which is as institute of Islamic education. Mosque as institute of implicit Islamic education, developed first time by Burhanuddin's Sheikh at Ulakan Pariaman, and has tall keagamaan authority at minangkabau. But mosque role at Minangkabau starts to fade since early century 20. Which is is begun while Minangkabau's islamic community lies in situation that progressively is in a bind, since: first, economic pressure and Dutch colonial politics, both of, mark sense keagamaan's reconditioned idea.